Single cell transcriptome profiling reveals pathogenesis of bullous pemphigoid - Guirong Liang; Chenjing Zhao; Qin Wei; Suying Feng; Yetao Wang (Communications Biology)
Abstract Bullous pemphigoid (BP) triggers profound functional changes in both immune and non-immune cells in the skin and circulation, though the underlying mechanisms remain unclear. In this study, we conduct single-cell transcriptome analysis of lesional and non-lesional skin, as well as blood samples from BP patients. In lesional skin, non-immune cells upregulate pathways related to metabolism, wound healing, immune activation, and cell migration. LAMP3+DCs from cDC2 show stronger pro-inflammatory signatures than those from cDC1, and VEGFA+ mast cells, crucial for BP progression, are predominantly in lesional skin. As BP patients transition from active to remission stages, blood B cell function shifts from differentiation and memory formation to increased type 1 interferon signaling and reduced IL-4 response. Blood CX3CR1+ ZNF683+ and LAG3+ exhausted T cells exhibit the highest TCR expansion among clones shared with skin CD8+T cells, suggesting their role in fueling skin CD8+T cell clonal expansion. Clinical BP severity correlates positively with blood NK cell IFN-γ production and negatively with amphiregulin (AREG) production. NK cell-derived AREG mitigates IFN-γ-induced keratinocyte apoptosis, suggesting a crucial balance between AREG and IFN-γ in BP progression. These findings highlight functional shifts in BP pathology and suggest potential therapeutic targets.